SARS-CoV-2 Immunization Orchestrates the Amplification of IFNγ-Producing T Cell and NK Cell Persistence - La Sala, Lucia; Gandini, Sara; Bruno, Antonino; Allevi, Raffaele; Gallazzi, Matteo; Senesi, Pamela; Palano, Maria Teresa; Meregalli, Paola; Longhi, Ermanno; Sommese, Carmen; Luzi, Livio; Trabucchi, Emilio (Frontiers in Immunology, 2022)
A successful vaccination as a preventive strategy would represent the most efficient means to control the pandemic of Coronavirus Disease-19 (COVID-19) that lead to millions death worldwide. Novel vaccines mRNA-based confer protective immunity against SARS-CoV-2, but whether immunity is immediately effective and how long will remain in recipients are uncertain. Since the policy delay of boosts is considered, the assessment of the effectiveness of a single dose should be stated. Methods: A longitudinal cohort of health-care-workers (HCW, N=46; 30.4% men; 69.6% women; mean age 36.05±2.2 years old) with no SARS-CoV-2 infection as documented by negative polymerase chain reaction, were immunophenotyped in PBMC once a week for four weeks from the prime immunization (Pfizer mRNA BNT162b2) and had received 2 doses, to study the kinetic response. Results: We identified three risk groups to develop SARS-CoV2 infection IgG+-based (late-Responders, R-; early-Responders, R+; pauci-Responders, PR). In all receipts, the prevalence of IL4-producing B cells and IL4-producing CD8+ T cells, the early generation of B and NK cells, increased 24 hours after the 1^ dose. After the immunization, an imbalanced TH1/ TH2 response was observed concomitantly with a resistance of T cells, of IFNγ-producing CD4+T cells, IFNγ-producing NK cells. Also, a decline of hematologic parameters until the boost, coupled with a persistent increase of NK cells was found. The positive association (performed by multiple mixed effect model among serologic and hematologic parameters adjusted for confounders) of IFNg-producing NK with IFNg-producing CD4+T cells (p=0.036) suggest a relationship between these two subsets of lymphocytes. Also, the correlation matrix showed strong significance between IFNg-producing NK and IFNg-producing CD4+T cells (r=0.6, p<0.01). Conclusions: These findings introduce several concerns about policy delay in vaccination: based on immunological protection, B cells and the persistent increase of NK cells during 2 doses of mRNA-based vaccine could provide further immune protection against the virus, while CD8+ T cell increase slightly only in R+ and in the PR group.